Consuming the city: challenges and possibilities for foraging in Toronto's parks - Shortly, Anna; Kepe, Thembela (Forests, trees and livelihoods, 2021)
More often than not, foraging for wild products, such as berries, mushrooms, and weeds, is not currently permitted in many urban parks across North America. Nonetheless, foraging in urban green spaces is an ongoing and increasingly popular practice in many cities. Research has found that people forage in urban green spaces for reasons beyond supplementing their diet with wild foods, including cultivating a deeper connection with nature, maintaining cultural identities and practices, and participating in environmental stewardship. Acknowledging and legitimizing wild products in urban spaces has potential positive implications for fostering human-nature relationships in the city, and increasing equitable access and control over urban forest and green space resources. Drawing on a scan of foraging practices and edible landscaping projects and interviews with key informants in Toronto, Canada, this paper explores the opportunities and challenges of incorporating foraging practices into parks planning and management. The paper concludes that urban parkland managers should establish spaces for foraging, such as community orchards and food forests, in order to safely and sustainably accommodate foraging practices in public greenspaces alongside other uses.